Penggunaan Model Inkuiri Terbimbing untuk Meningkatkan Kemampuan Berpikir Kritis Fisika Siswa SMA - Nirmala Respatiningrum; Sunardi Sunardi; Muhammad Akhyar (Universitas Sebelas Maret, 2017)
One of the goals of science education in Indonesia is to produce quality students, namely people who are able to think critically, creatively, logically and take initiative, in responding to issues that develop in society. Students' critical thinking skills can be improved through the learning model used, so this study aims to determine the effect of guided inquiry models in improving critical thinking skills. This research is qualitative research. The subject of this research is high school students. Data collection techniques in this study were interviews, observation, and tests. The validity of the data used is data triangulation. The results of this study indicate that the use of guided inquiry models in physics can improve the critical thinking skills of high school students